Cluster analysis for outlier detection : A case study of applying unsupervised machine learning on diesel engine data - Westerlund, Otto (My University, 2023)
With the advent of modern data driven methods, engine manufacturers and maintainers are attempting to pivot from corrective to predictive maintenance. One way to achieve this goal is to install sensors on the engine and look for anomalies in the data patterns it produces. Companies such as Wärtsilä that provide condition monitoring services use the Fast Fourier Transform to manually look for anomalies in the data. The Edge-project is an industrial research project involving institutions such as universities and private companies, with the goal of developing technical solutions and edge analytics for autonomous devices and vessels. Several papers and theses have been written as a result of the project, using techniques such as autoencoders to perform anomaly detection on data produced by sensors on a diesel engine. This thesis explores the use of cluster analysis for anomaly detection on diesel engine data from the Edge-project. Finding clusters could potentially represent different states of the running engine, with anomalies being represented e.g. by data points far away from cluster centroids, or data points not belonging to any particular cluster. The techniques of K-means, DBSCAN and spectral clustering are used for assigning clusters, with silhouette coefficient and eigengap used as hyperparameter tuning heuristics. Distance from cluster centroids and reduced kernel density estimation are used to flag anomalies. T-SNE and Self-Organizing Maps are used as dimensionality reduction techniques to visualize the data into a 3-dimensional and 2-dimensional space, respectively. Results show that what data are flagged as anomalies is highly sensitive to the choice of algorithm and chosen hyperparameters. The different results suggest different data as anomaly candidates. Therefore, further evaluation is needed from subject matter experts to determine which one of the models provides the most interesting results. Further work could include building an ensemble model that combines the used approaches, which could flag certain areas of the data space as a high risk for being anomalous.

Moottorien valmistajat ja ylläpitäjät pyrkivät siirtymään korjaavasta huollosta ennakoivaan huoltoon modernien datavetoisten menetelmien avulla. Tämä voidaan saavuttaa esimerkiksi asentamalla antureita moottoriin ja etsimällä poikkeavuuksia anturien tuottamasta datasta. Yritykset kuten Wärtsilä, jotka tarjoavat kunnonvalvontapalveluita etsivät datasta poikkeavuuksia manuaalisesti Fourier-muunnosten avulla. Edge-projekti on teollinen tutkimushanke, johon osallistuu mm. yliopistoja ja yksityisen sektorin yrityksiä, ja jonka tavoitteena on tuottaa teknisiä ratkaisuja ja reunalaskenta-analytiikkaa itseohjautuville laitteille, ajoneuvoille ja aluksille. Hankkeesta on kirjoitettu monia tutkimusartikkeleita ja opinnäytetöitä, joissa käytetään tekniikoita kuten syviä neuroverkkoja poikkeavuuksien havaitsemiseen dieselmoottoriin asennettujen anturien tuottamasta datasta. Tämä opinnäytetyö tutkii klusterianalyysiä menetelmänä poikkeavuuksien havaitsemiseen Edge-projektissa ajetun dieselmoottorin datasta. Klusterit voisivat mahdollisesti edustaa ajettavan moottorin eri tiloja, ja poikkeavuudet voisivat olla esim. kaukana klusterien keskipisteistä olevia datapisteitä, tai datapisteitä, jotka eivät kuulu mihinkään tiettyyn klusteriin. Työssä käytetään algoritmeja K-means, DBSCAN ja spektraaliklusterointia klusterien määrittämiseen, ja siluettikerrointa sekä ominaisväliä käytetään hyperparametrioptimoinnin heuristiikkoina. Poikkeavuuksien merkintään käytetään etäisyyttä klusterien keskipisteisiin sekä alennettua ydintiheysestimaattoria. T-SNE:tä ja itseorganisoituvaa karttaa käytetään datan ulottuvuuksien vähentämisen tekniikoina, jotta data voidaan visualisoida 3- ja 2-ulotteiseen avaruuteen. Tulokset osoittavat, että mikä data tulkitaan poikkeavana, riippuu vahvasti algoritmin ja sen hyperparametrien valinnasta. Menetelmien merkitsemät poikkeavuudet eroavat huomattavasti toisistaan. Tämän vuoksi vaaditaan aihealueen ammattilaisilta lisätutkimuksia, jotta voidaan päättää mikä malli luo mielenkiintoisimmat tulokset. Jatkokehitysideana voisi olla mallikokoelma, jossa yhdistyy tässä työssä käytetyt menetelmät, ja jonka tehtävänä olisi kartoittaa data-avaruuden eri alueiden riskit poikkeavuuksien sisältämiseen.
Keywords: Cluster analysis, algorithm, engine, unsupervised learning, anomaly detection, edge computing